Kinerja Keuangan Memediasi Pengaruh Corporate Social Responsibility dan Struktur Modal Terhadap Nilai Perusahaan - Sutriningsih, Sutriningsih; Handajani, Lilik; Rifa'i, Ahmad (E-Jurnal Akuntansi, 2019)
The study aims to examine the effect of corporate social responsibility and capital structure on firm value with financial performance as an intervening variable. The research population is a manufacturing company listed on the Indonesia Stock Exchange in 2015-2017 and discloses corporate social responsibility. The sample was determined by purposive sampling obtained 114 samples. The data analysis tool uses path analysis. The findings of the study indicate that financial performance (ROE) cannot function as an intervening variable in the effect of CSR on the value of the company in the BEI manufacturing company in the period 2015-2017. Whereas the capital structure of financial performance that is proxied by ROE in this study can function as an intervening variable. The implications of this research can be useful as a consideration for companies in making policies related to disclosure of corporate social responsibility. Keywords: Corporate social responsibility, capital structure, financial performance, company value.